2011
DOI: 10.1161/circep.110.961615
|View full text |Cite
|
Sign up to set email alerts
|

SERCA2a Gene Transfer Decreases Sarcoplasmic Reticulum Calcium Leak and Reduces Ventricular Arrhythmias in a Model of Chronic Heart Failure

Abstract: Background Sarcoplasmic reticulum calcium ATPase 2a (SERCA2a) gene therapy improves mechanical function in heart failure, and is under evaluation in a clinical trial. A critical question is whether SERCA2a gene therapy predisposes to increased sarcoplasmic reticulum calcium (SR Ca2+) leak, cellular triggered activity and ventricular arrhythmias in the failing heart. Methods and Results We studied the influence of SERCA2a gene therapy upon ventricular arrhythmogenesis in a rat chronic heart failure model. ECG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 42 publications
10
144
0
5
Order By: Relevance
“…4c). This result is in agreement with the reduction in provokable ventricular arrhythmias observed following SERCA-2a gene therapy in a swine infarction model attributable to stabilization of SR calcium loading 53 .…”
Section: Resultssupporting
confidence: 89%
“…4c). This result is in agreement with the reduction in provokable ventricular arrhythmias observed following SERCA-2a gene therapy in a swine infarction model attributable to stabilization of SR calcium loading 53 .…”
Section: Resultssupporting
confidence: 89%
“…In these earlier studies, SERCA2a gene therapy was effective in suppressing triggered activity by reducing SR calcium leak and spontaneous calcium waves 7. Unlike in rodents, however, complex arrhythmias in humans and large animals require an appropriate electrophysiological substrate that converts calcium‐mediated triggers into sustained VT/VF.…”
Section: Discussionmentioning
confidence: 99%
“…A key question is whether accelerating intracellular Ca 2+ cycling using SERCA2a gene therapy suppresses or promotes post‐MI arrhythmias. In rodents, SERCA2a overexpression ameliorated triggered activity by decreasing ryanodine receptor–mediated Ca 2+ leak 7. However, unlike in rodents, post‐MI arrhythmias in large animals and humans require an adverse electrophysiological substrate that is capable of converting Ca 2+ ‐mediated triggers to sustained VT/VF.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a number of studies have shown beneficial effects on cardiac structure, contractility, Ca cycling (including reduced Ca leak), and myocardial energetics after SERCA gene delivery, either via direct intramyocardial injection or via coronary perfusion, in diverse models of heart failure. [26][27][28][29] There are several potential problems that may arise as a consequence of attempts to increase SERCA activity in heart failure. These include an increase in energy/oxygen demand because of the requirement for ATP hydrolysis to drive the increased Ca transport by SERCA.…”
Section: Targeting Serca Directly-from Bench To Clinical Trialmentioning
confidence: 99%